Short-Term Regulation of FcγR-Mediated Phagocytosis by TLRs in Macrophages: Participation of 5-Lipoxygenase Products - Carla da S. Pinheiro; Ana Paula T. Monteiro; Fabiano F. Dutra; Marcelo T. Bozza; Marc Peters-Golden; Claudia F. Benjamim; Claudio Canetti (Hindawi Limited, 2017)
TLRs recognize a broad spectrum of microorganism molecules, triggering a variety of cellular responses. Among them, phagocytosis is a critical process for host defense. Leukotrienes (LTs), lipid mediators produced from 5-lipoxygenase (5-LO) enzyme, increase FcγR-mediated phagocytosis. Here, we evaluated the participation of TLR2, TLR3, TLR4, and TLR9 in FcγR-mediated phagocytosis and whether this process is modulated by LTs. Rat alveolar macrophages (AMs), murine bone marrow-derived macrophages (BMDMs), and peritoneal macrophages (PMs) treated with TLR2, TLR3, and TLR4 agonists, but not TLR9, enhanced IgG-opsonized sheep red blood cell (IgG-sRBC) phagocytosis. Pretreatment of AMs or BMDMs with drugs that block LT synthesis impaired the phagocytosis promoted by TLR ligands, and TLR potentiation was also abrogated in PMs and BMDMs from 5-LO−/− mice. LTB4 production induced by IgG engagement was amplified by TLR ligands, while cys-LTs were amplified by activation of TLR2 and TLR4, but not by TLR3. We also noted higher ERK1/2 phosphorylation in IgG-RBC-challenged cells when preincubated with TLR agonists. Furthermore, ERK1/2 inhibition by PD98059 reduced the phagocytic activity evoked by TLR agonists. Together, these data indicate that TLR2, TLR3, and TLR4 ligands, but not TLR9, amplify IgG-mediated phagocytosis by a mechanism which requires LT production and ERK-1/2 pathway activation.